2002
DOI: 10.1209/epl/i2002-00471-9
|View full text |Cite
|
Sign up to set email alerts
|

Vibrations of amorphous, nanometric structures: When does continuum theory apply?

Abstract: Abstract. -We investigate the low frequency end of the vibrational spectrum in small (nanometric) disordered systems. Using numerical simulation and exact diagonalization for simple two dimensional models, we show that continuum elasticity, applied to these systems, actually breaks down below a length scale of typically 30 to 50 molecular sizes. This length scale is likely related to the one which is generally invoked to explain the peculiar vibrational properties of glassy systems.Determining the vibrational … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
163
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(179 citation statements)
references
References 18 publications
16
163
0
Order By: Relevance
“…In the figure, we have plotted the (normalized) correlation function Interestingly, it can be readily shown that We demonstrate now that the non-affine displacement field in 3D is indeed of predominantly solenoidal nature. This has been anticipated by our previous studies on 2D systems [1] and by the values of the elastic moduli µ and K discussed in Sec. III C. The transverse and longitudinal contributions to the displacement field can be numerically obtained by computing…”
Section: Correlations In the Non-affine Displacement Fieldsupporting
confidence: 76%
See 4 more Smart Citations
“…In the figure, we have plotted the (normalized) correlation function Interestingly, it can be readily shown that We demonstrate now that the non-affine displacement field in 3D is indeed of predominantly solenoidal nature. This has been anticipated by our previous studies on 2D systems [1] and by the values of the elastic moduli µ and K discussed in Sec. III C. The transverse and longitudinal contributions to the displacement field can be numerically obtained by computing…”
Section: Correlations In the Non-affine Displacement Fieldsupporting
confidence: 76%
“…The second frequency has degeneracy 24, and so on. In our previous analysis of 2D systems [1], we found that this…”
Section: Low Frequency Equilibrium Vibration Modesmentioning
confidence: 60%
See 3 more Smart Citations